1982
DOI: 10.1515/znb-1982-1113
|View full text |Cite
|
Sign up to set email alerts
|

Zweikernige und dreikernige Carbonyleisenkomplexe mit 1.2-und 1.3-Dithiolatobrückenliganden / Dinuclear and Trinuclear Carbonyliron Complexes Containing 1,2-and 1,3-Dithiolato Bridging Ligands

Abstract: The reactions of 1,2- and 1,3-dithioles, HSRSH, with Fo3(CO)12 give the dinuclear compounds Fe2(CO)6(SRS) in good yields. With R = C2H4 or R = C3H6 the trinuclear compounds (CO)3Fe(SRS)Fe(CO)(SRS)Fe(CO)3 containing an open Fe3 chain are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
103
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(109 citation statements)
references
References 4 publications
5
103
1
Order By: Relevance
“…Whereas 1,3-disulfanylpropan-2-ol reacts with Fe 3 (CO) 12 in the usual way to form a dinuclear complex 1, 1,4-disulfanylbutane-2,3-diol leads, under (2) C (1)ÀC (2) C (3)ÀC (2) O (1)ÀC (2) s similar reaction conditions, to a tetranuclear complex 2. Here, the dithiolato ligands are coordinated to two different Fe 2 (CO) 6 moieties. The DFT calculation for 1 showed that the unexpected bonding situation is not a packing effect, but it is to be attributed to the influence of the O-atom, according to the …”
Section: S(1)àfe(1)às(2) 854 S(1)àc(1)àc(2) 1174 S(1)àfe(2)àsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas 1,3-disulfanylpropan-2-ol reacts with Fe 3 (CO) 12 in the usual way to form a dinuclear complex 1, 1,4-disulfanylbutane-2,3-diol leads, under (2) C (1)ÀC (2) C (3)ÀC (2) O (1)ÀC (2) s similar reaction conditions, to a tetranuclear complex 2. Here, the dithiolato ligands are coordinated to two different Fe 2 (CO) 6 moieties. The DFT calculation for 1 showed that the unexpected bonding situation is not a packing effect, but it is to be attributed to the influence of the O-atom, according to the …”
Section: S(1)àfe(1)às(2) 854 S(1)àc(1)àc(2) 1174 S(1)àfe(2)àsmentioning
confidence: 99%
“…By using 1,4-disulfanylbutane-2,3-diol [6] and 1,3-disulfanylpropan-2-ol, we aimed at creating two novel model complexes as shown in Scheme 2. The reactions of the disulfanyl compounds with dodecacarbonyltriiron in refluxing THF or toluene are presented in this contribution.…”
mentioning
confidence: 99%
“…The parent model, (-pdt)Fe 2 (CO) 6 (35) is a complex that reproduces the Fe 2 S 2 core fairly faithfully (36), including the three-light-atom S-to-S linker (Fig. 1).…”
mentioning
confidence: 91%
“…On an entirely different time scale, chemists have established the ability of the diirondisulfide of (-S 2 )Fe 2 (CO) 6 unit to mediate organic transformations at sulfur (33,34), including the synthesis of model complexes (35) of import to the discussion below. The parent model, (-pdt)Fe 2 (CO) 6 (35) is a complex that reproduces the Fe 2 S 2 core fairly faithfully (36), including the three-light-atom S-to-S linker (Fig.…”
mentioning
confidence: 99%
“…For the structures of similar trinuclear mixed-valence iron complexes, see : Winter et al (1982); Ghosh et al (2011).…”
Section: Related Literaturementioning
confidence: 99%